Descriptions of diplostomid metacercariae (Digenea: Diplostomidae) from freshwater fishes in the Tshwane area - Esmey B.E. Moema (Onderstepoort Journal of Veterinary Research, 2013)
The metacercarial (larval) stages of diplostomid digeneans are known to inhabit freshwater fish, causing tissue damage in the process. Due to their widespread diversity, little is known about their life cycle. The classification of these parasitic stages to the species level using only the morphology is very challenging due to the lack of genitalia; they are regarded to be the most important structures in the identification of these organisms. In this study, additional morphological information through light and scanning electron microscopy is given for two different diplostomids found in the cranial cavity of Clarias gariepinus and the vitreous chambers of Tilapia sparrmanii and Pseudocrenilabrus philander. The diplostomid metacercaria inhabiting the cranial cavity of Clarias gariepinus was morphologically identified as Diplostomulum (Tylodelphys) mashonenseand an unknown metacercaria of the genus Diplostomumwas found in the vitreous chambers of Pseudocrenilabrus philander and Tilapia sparrmanii. Both parasitic species’ 28S recombinant deoxyribonucleic acid genomic regions were successfully amplified using Dig 125/1500R primer pairs. The assay yielded a product of approximately 1300 base pairs as seen on the gel images. There were 14 nucleotide differences over the entire analysed sequences resulting in a 1.1% (14/1273) nucleotide difference. In line with the morphological characteristics of these parasites, there seemed to be a slight difference in their genetic makeup. The application of molecular techniques on digenetic trematodes seems very promising and may yield great potential in future descriptions of morphologically similar parasitic species.